THE USE OF CODE MIXING BETWEEN INDONESIA AND ENGLISH LANGUAGE ON RUANG SANDI PODCAST - Elisabeth Ernesta Meda; Rikardus Nasa (Universitas Padjadjaran, 2023)
The purpose of the research was to find out the forms of code mixing and the dominant forms of code mixing used by podcaster and guest star on Ruang Sandi podcast. The researcher took the data from six videos on Ruang Sandi podcast, from June 2020 until January 2021, especially the woman guest stars aged 20 to 30 years. This research was descriptive qualitative. The researcher used documentation method in collecting the data and then the data were classified using Suwito’s theory and presented in table form. Based on the result of the study, the researcher found that there were 705 code mixing consisting of 290 insertion of word, 216 insertion of phrase, 75 insertion of hybrid, 18 insertion of reduplication, 11 insertion of idiom, and 95 insertion of clause. The dominant forms was insertion of word with the percentage 41,13%.